ANALISIS FAKTOR YANG MEMENGARUHI KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI UPT PUSKESMAS MERAL - Sugiyarningsih; Devy Lestari Nurul Aulia (Universitas Batam, 2023)
Chronic energy deficiency in pregnant women is a problem that still occurs today. Chronic energy deficiency in pregnant women can have an impact on the mother's health during pregnancy, childbirth and the health condition of the child to be born. This study used an observation method with a cross-sectional design which aims to determine the factors that influence the incidence of CED in pregnant women at UPT Puskesmas Meral. The population in this study were 167 pregnant women, there were 42 pregnant women who were used as research samples using cluster sampling technique. The factors that influence the occurrence of SEZ are analyzed using multiple logistic regression tests with a 95% confidence level. The results of this study indicate that the income of pregnant women who are classified as below the minimum wage is the most influential independent variable for experiencing chronic energy deficiency (KEK) in pregnant women (p-value 0.208).